Musealization in Consultative Archeology Projects: Heritage Perspectives for the Carajás Railway (MA/PA) (Cadernos de Sociomuseologia, 2016)
ln this work I deal with the issue of musealization of archaeological research that is being carried out all over Brazil in the context of Brazilian economic growth and environmental licensing process. I focus my considerations on the adverse impact of  development on the Brazilian Heritage; for it is known that even when issues related to the archaeology research are properly equated, little has been done on matters of collection management, preservation, and promoting heritage, especially for local community. These issues are within the scope of musealization process, which unfolds tensions between heritage preservation and Consulting Archaeology.I emphasize the understanding of the role that Museology can play in the interfaces between heritage - society - development; and the interdisciplinary perspective for the application of these principles in new musealization processes.Hence, I begin with the hypothesis that museological process has the potential lo support a positive dialogue between Consulting Archaeology and Society, ensuring strategies of knowledge extroversion and heritage education. Taking into consideration the assumptions of Sociomuseology, I discuss musealization issues posed by archaeological research carried out along the Carajás Railroad, located in the Eastern Brazilian Amazon. Key words: Sociomuseology - Archaeology's Musealization - Consulting Archaeology Heritage Education - Heritage Preservation